Inequality among brothers class and kinship in South China - Watson, Rubie S. 1945- (Cambridge studies in social and cultural anthropology, 1985)
Using historical documents and evidence gathered in the field, Rubie Watson provides a social history of the 600-year-old Chinese lineage village of Ha Tsuen in the New Territories of Hong Kong, and demonstrates the crucial role that the lineage played in the evolution of the community from a few scattered households in the fourteenth century into a regional power from the 1700s onwards. Despite a patrilineal ideology that extols the virtues of brotherhood and equality, Dr Watson shows that the lineage has in fact played a central role in the formation, development and maintenance of an élite class of landlords and merchants, who, even though their economic importance has now declined, continue to exert political control. Dr Watson examines the dynamics of interclass relations within a single lineage and shows how these relations have been transformed as a consequence of the growth of wage labour